Communication Management in Creating Ideal Interactions in Greend Spaces - Sri Prasetyo Widodo; Dwi Purwanto; Herwin Siregar; Parulian Naibaho; Ardhien Rafa; Sindi Sagita; Siti Nurjannah; Fitria Nonita; Risna winarti; Ejar Fadilah; Muji Indarwanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aims of this study are: 1. To describe the reasons for the need for communication skills when implementing KKN. 2. Describe the obstacles related to communication experienced by KKN participants at Mpu Tantular University, Jakarta while participating in the KKN program. 3. Describe student impressions of the KKN program. This research is a type of qualitative research with an ethnographic approach. The object of this study was the communication skills of FIKOM and Engineering students, the subjects were KKN participants at Mpu Tantular University, Jakarta. The results of this study indicate that in the implementation of KKN communication skills are very useful in the process of adaptation to the community, the process of approaching the community, to create good relations with the community, organizing residents to participate in the implementation of KKN and cultivating a friendly attitude. There were several obstacles experienced by participants related to communication, namely difficulties in explaining the work program to be carried out at the KKN location, organizing students who were passive to participate in activities and sometimes misunderstandings occurred between participants. This KKN program is a program that can provide experience and make students more aware of cleanliness and create a greedy workspace.